A comparative investigation into the representation of Russia in apartheid and post-apartheid era South African History textbooks (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In this comparative study we employed a quantitative approach, underpinned by the interpretivist paradigm, to analyse the content on Russia as found in Apartheid and post-Apartheid History textbooks. This was done by means of qualitative content analysis. The focus of the analysis was exclusively on the historical content or substantive knowledge as it related to Russia. What emerged was that the political eras Russia was studied under remained remarkably similar across the Apartheid and post-Apartheid eras. However, clear discernible similarities and differences were otherwise detectable. While big men dominated the content of both eras the approach adopted by the post-Apartheid era History textbooks towards them were generally more critical. While a fear of Communism was imbedded in the Apartheid era History textbooks, the opposite can be said of the post-Apartheid era textbooks. What this points to is that during both political eras the content on Russia was adapted to suit the prevailing identity politics, national narratives and ideology of the time – closed and insular under Apartheid and open and critical in the post-Apartheid era.
Keywords: Russia; South Africa; History textbooks; Apartheid; PostApartheid; Ideology